Manganese mediates antiviral effects by driving an ATM -TBK1 phosphorylation signaling pathway - Sui, Hongyan; Wiscovitch-Russo, Rosana; Cachaco, Silvia; Yang, Jun; Bruchey, Whitney; Laverdure, Sylvain; Chen, Qian; Imamichi, Tomozumi (Frontiers in Immunology, 2025)
Ataxia-telangiectasia mutated (ATM) is traditionally recognized as a nuclear kinase involved in DNA damage repair. We were the first to report that ATM also participates in a manganese (Mn)-dependent TBK1 phosphorylation pathway. However, the underlying mechanism by which how Mn induces TBK1 phosphorylation through ATM remained unclear. Here, we show that Mn dose-dependently induced TBK1 phosphorylation in the presence of ATM across multiple cell lines, as well as in primary human macrophages and T cells. This phosphorylation was abolished in ATM-deficient cells, and we identified cytoplasmic ATM as a key mediator. Immunoprecipitation assays revealed that Mn promoted ATM phosphorylation at Ser1891, Ser1981, and Ser2996. TBK1 interacted with phosphorylated ATM at early stages, but upon phosphorylation, TBK1 dissociated from the ATM–TBK1 complex. This dissociation coincided with enhanced antiviral cytokine production. Furthermore, Mn inhibited HIV replication in a dose-dependent manner by inducing multiple antiviral host factors and cytokines, with Mn-dependent ATM-TBK1 phosphorylation pathway being patricianly involved. Together, these findings identify a cytoplasmic ATM–TBK1 phosphorylation cycle as one of essential regulators of antiviral innate immunity and suggest Mn supplementation as a potential therapeutic approach against HIV and other viral infections.